Phonological Structure of Indonesian and Vietnamese Language: A Contrastive Analysis - Sumarti, Sumarti; Rusminto, Nurlaksana Eko; Burhanudin, Burhanudin (Jurnal Pendidikan Progresif, 2021)
Phonological Structure of Indonesian and Vietnamese: A Contrastive Analysis. Objectives: The objectives of this study were to describe the differences in the phonological structure of Indonesian and Vietnamese. Methods: In this case study qualitative research, the informant is a Vietnamese-speaking student who is studying Indonesian. Data was collected through interviews and observations and analyzed by identifying similarities and differences in phonological structure data, coding the data, analyzing and describing the data, and reflecting them as research findings. Findings: The differences in the phonological structure of Indonesian and Vietnamese are (1) spectacle and tonal structures; (2) bisyllabic and monosyllabic syllable structures; (3) the number of vowels, consonants, and diphthongs. Conclusion: This difference in phonological structure makes it difficult for Vietnamese speakers to pronounce Indonesian sounds. This finding becomes a design for the preparation of materials and Indonesian language learning for foreign speakers from Vietnam.Keywords: contrastive analysis, phonological structure, language typology.DOI: http://dx.doi.org/10.23960/jpp.v11.i3.202122